SOCIAL CAPITAL IN MANAGING MANGROVE AREA AS ECOTOURISM BY MUARA BAIMBAI COMMUNITY - Situmorang, Rospita Odorlina (Indonesian Journal of Forestry Research, 2018)
The success of managing the natural environment by involving the community is strongly influenced by the local social conditions. This paper analyzes social capital inherent in the Muara Baimbai Community in Sei Nagalawan Village to manage the mangrove forest as an area valued for tourism. The study was conducted in Muara Baimbai Mangrove Area, Sei Nagalawan Village, Perbaungan District, Serdang Bedagai Regency on June until December 2014. Data were collected by observation, interview using a structured questionnaire, and in-depth interviews. The Muara Baimbai Community has strong social capital in managing the mangrove ecotourism area. An indicator of a strong social capital is a community institution which is run properly. The success of the community to rehabilitate the mangrove area in Sei Nagalawan and to utilise its resources in a sustainable manner is the result of high levels of participation of the members and the role of active cadres as symbolic power that encourage, drive, and motivate the community in their struggle. Strong motivation, fair work allocation and benefits among the members, strong internal connection, and wide external network are very important to strengthen social capital. Furthermore, the increasing welfare gained by the coastal community through increasing economic income, job opportunities, and knowledge are the benefits derived from the sustainable forest management that can maintain the existence of the community and their natural resource